The application of gradually expanding pedicle technology in the placement of screws in thinner pedicle of patients with idiopathic scoliosis - Chen, Fei; Li, Jianyi; Li, Tao; Xi, Yongming (Frontiers in Surgery, 2024)
Objective To propose a technique of gradual expansion of pedicle diameter to place screws on the thinner pedicle that is difficult to place screws in scoliosis orthopedic surgery, in order to place thicker pedicle screws in the premise of good safety to achieve good stability and orthopaedic effect. Methods The authors reviewed that 36 patients with Adolescent idiopathic scoliosis (AIS) (20 females, 16 males) in our department from June 2020 to March 2024 underwent posterior spinal correction and internal fixation were enrolled in the present study. 194 pedicles had narrower diameter ranging from 0 mm to 4.5 mm. After analysis, 155 pedicles (internal diameter: 2.5 mm–4.5 mm) were treated with gradually expanding pedicles technology. The angle between the inserted screws and the upper endplate of the vertebral body was measured 1 week after operation and 3 months after operation to evaluate the placement of the screws after pedicle expansion. Results All operations were completed without dura mater rupture, nerve root injury, infection and poor incision healing. There was no screw breaking or screw pull-out in DR film at 3 months after operation compared with 1 week after operation. There was no significant difference in the angle between screw and upper endplate measured by the three observers at 3 months and 1 week after operation (Wilcoxon's signed rank test, p > 0.05). In the measurement at 1 week or 3 months after operation, there was no statistically significant difference among the three observers. There is a good consistency between the observers (Cronbach's alpha > 0.80). Conclusion In AIS patients, the thinner pedicle with a diameter range of 2.5 mm to 4.5 mm can be safely inserted with relatively thicker pedicle screws after gradually expanding pedicle technology.